Ciclo de melhoria da qualidade na prevenção de flebite em uma maternidade-escola - Souza, Francisco Lindomar de (2022)
Introduction: Intravenous therapy (IVT) is part of nursing's routine in the treatmen tof health problems, beingdefined as a set of knowledge and techniques aimed at administering solutions or drugs in the circulatory system through central or peripheral access. It stands out among the essential technologies to ensure the survival of patients. However, it is a source of pain and can cause several serious complications, including phlebitis. Methodology: quasi-experimental, before-and-after study, with a time series, quantitative and qualitative approach, carried out in the high-risk ward of Maternidade Escola Januário Cicco (MEJC), through an intervention with an improvement cycle in the period between May and October 2022, in five phases: (1) Identification and prioritization of the improvement opportunity; (2) Analysis of the opportunity for improvement; (3) Quality assessment; (4) Intervention to improve; (5) Reassessmentand record of the improvement achieved. Results: The intervention consisted of a training course given by the master's student with nursing professionals working in the high-risk ward. Ten quality criteria related to the care process in IVT were selected, considered useful to assess the improvement in the quality of phlebitis prevention. For this purpose, indicators of puncture and maintenance of peripheral intravenous catheter pre- and post-interventions were monitored and the level of compliance with the evaluated criteria was calculated. Absolute compliance was identified in two criteria: C1- Performing hand hygiene before and after in sertion of the peripheral catheter, with 100% compliance and C5- Use of peripheral catheters over needle. The criteria with levels of non-compliance were: C3- Use of transparent semipermeable and sterile covering for stabilization of peripheral vascular accesses;C8- Protect the coverage of the peripheral vascular access with plastic and/or aluminum foil while bathing the patient; C9: Use syringes filled with 0.9%salinesolution to administer flushing in the peripheral vascular access; and C10- Daily assessment of the insertion site of the peripheral vascular access by thenurse, monitoring the maintenance time of the catheter, which should not exceed 96 hours. After the interventions, the quality criteria were again evaluated. It was found that there were changes in the levels of fulfillment of the criteria evaluated positively, with significant improvements in most of the criteria. Conclusion: The implementation of a quality improvement cycle in the prevention of phlebitis proved to be relevant for patient safety and encouraged the adoption of practices based on scientific evidence by nursing professionals before and after the intravenous catheterization process.